Efek Kepuasan Hidup pada Pengobatan Sarcoidosis - Milna Sari; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing; Romaito Nasution (Pusat Riset dan Inovasi Nasional, 2024)
This meta-analysis investigated the effect of life satisfaction on Sarcoidosis treatment outcomes across 47 studies encompassing 8,932 patients. The findings revealed a significant positive correlation between life satisfaction and treatment success (r = 0.62, p < 0.001). Patients with high life satisfaction scores (>7.5/10) demonstrated a 73% higher likelihood of achieving remission compared to those with low scores (<5/10) (OR = 2.84, 95% CI: 2.31-3.49). Regression analysis indicated that each one-point increase in life satisfaction scores was associated with an 18% reduction in Sarcoidosis relapse rates (β = -0.18, p = 0.002). Treatment adherence and health behaviors were found to mediate the relationship between life satisfaction and Sarcoidosis treatment outcomes, accounting for 42% and 35% of the variance, respectively. Moderator analyses demonstrated stronger effects among patients with disease duration <5 years (p = 0.011) and those with mild to moderate disease severity (p = 0.003). These findings extend the work of Lee et al. (2020) and Martínez-García et al. (2021) by demonstrating a more pronounced effect of life satisfaction on Sarcoidosis treatment compared to other chronic conditions. Notably, contrary to Saketkoo et al (2021) previous study, the effect of life satisfaction remained significant even after controlling for patients' socioeconomic factors (β = 0.41, p < 0.001). These results underscore the crucial role of psychosocial interventions in enhancing Sarcoidosis treatment efficacy, offering new perspectives in the management of this chronic condition.